Diels-Alder Cycloaddition Reactions in Sustainable Media - Soares, Maria I. L. (2022)
Diels-Alder cycloaddition reaction is one of the most powerful strategies for the construction of six-membered carbocyclic and heterocyclic systems, in most cases with high regio- and stereoselectivity. In this review, an insight into the most relevant advances on sustainable Diels-Alder reactions since 2010 is provided. Various environmentally benign solvent systems are discussed, namely bio-based derived solvents (such as glycerol and gluconic acid), polyethylene glycol, deep eutectic solvents, supercritical carbon dioxide, water and water-based aqueous systems. Issues such as method's scope, efficiency, selectivity and reaction mechanism, as well as sustainability, advantages and limitations of these reaction media, are addressed.